Analysis of the Effect of Family Support and Knowledge of Arv Therapy in Patients With HIV on Quality of Life With Adherence to Taking Arv Drugs as an Intervening Factor in the Outpatient Unit of RSUD Kabupaten Tangerang - Tasya Sabrina Chairunisa; Intan Silviana Mustikawati; Kemala Rita (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Human Immunodeficiency Virus (HIV) remains one of the most serious health challenges in the world. Until now, people with HIV/AIDS have not been cured, but HIV infection and replication can still be prevented with medication. The treatment is known as antiretroviral therapy (ARV). Quality of life in HIV/AIDS patients is very important to note, because this infectious disease is chronic and progressive, so that it has an impact on various aspects of life, both physical, psychological, social, and spiritual. This study aims to identify factors that can affect the quality of life of HIV/AIDS patients through family support, knowledge of ARV therapy, and adherence to taking medication as intervening. Quantitative research method with cross sectional design. The sample technique in this study was purposive sampling. The minimum sample size was determined through Hair's formula and 140 samples were obtained. Data collection techniques with questionnaires and data analysis techniques using bivariate and multivariate analysis. The results showed that there was a significant positive influence between family support and knowledge of ARV therapy on quality of life through adherence to taking ARV drugs as an intervening variable. There is a significant positive influence between family support on quality of life. There is a significant positive influence between ARV therapy knowledge on quality of life. There is a significant positive influence between family support on adherence to taking ARV drugs. There is a significant positive influence between knowledge of ARV therapy on adherence to taking ARV drugs. There is a significant positive influence between adherence to taking ARV drugs on quality of life.